2018
DOI: 10.18632/oncotarget.24148
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of toxicity of 5-fluorouracil, doxorubicin and cyclophosphamide chemotherapy in breast cancer patients

Abstract: The differences in patients’ response to the same medication, toxicity included, are one of the major problems in breast cancer treatment. Chemotherapy toxicity makes a significant clinical problem due to decreased quality of life, prolongation of treatment and reinforcement of negative emotions associated with therapy.In this study we evaluated the genetic and clinical risk factors of FAC chemotherapy-related toxicities in the group of 324 breast cancer patients. Selected genes and their polymorphisms were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 111 publications
2
47
0
1
Order By: Relevance
“…Our results are consistent with the results of Lal et al 2007, that SNPs in SLC22A16 are associated with shorter OS and PFS in Asian breast cancer patients 51 . Furthermore, earlier studies confirmed the association of SNPs within SLC22A16 with toxic side effects in chemotherapy in breast cancer patients 36,50,52 . Additionally, overexpression of SLC22A16 in cancer cells is associated with the increasing influx of doxorubicin into cell and correlates with increased sensitivity to cytotoxic effects of this drug 53 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Our results are consistent with the results of Lal et al 2007, that SNPs in SLC22A16 are associated with shorter OS and PFS in Asian breast cancer patients 51 . Furthermore, earlier studies confirmed the association of SNPs within SLC22A16 with toxic side effects in chemotherapy in breast cancer patients 36,50,52 . Additionally, overexpression of SLC22A16 in cancer cells is associated with the increasing influx of doxorubicin into cell and correlates with increased sensitivity to cytotoxic effects of this drug 53 .…”
Section: Discussionmentioning
confidence: 66%
“…Stepwise regression made possible to obtain data on independent prognostic factors (p ≤ 0.05) of FAC chemotherapy. Cumulative analyzes enabled us to estimate the risk of non-response to the therapy for two or more independent factors, as described previously 36 .…”
mentioning
confidence: 99%
“…The pore size diameter, calculated according to Barrett, Joyner, and Halenda (BJH) was 9.8 nm (98 Å) (from desorption branch), with a cumulative surface area of 710. 36 Post-grafting was utilised to functionalise the surface of the MSNs, by protonating their outer surface and increasing their hydrophilicity [46]. This contributed to the enlarged hydrodynamic sizes from NTA (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…These cytostatic or cytotoxic compounds usually have low bioavailability and are thus administered at high dosages or for prolonged dosing intervals, leading to systemic side effects at non-specific sites [19,20].Doxorubicin (DOX) remains one of the most efficient anthracycline drugs available and is used in the treatment of diverse cancers, including breast, cervical, bone, gastric and leukaemia [21][22][23]. Despite its popularity, its low solubility [24][25][26], coupled with increased dosing frequencies [27][28][29] has resulted in many associated side effects, including cardiotoxicity [30][31][32], myelosuppression [33,34], induced vomiting with nausea [35,36], and alopecia [18,37]. Critical evaluation of these detrimental side-effects that become more pronounced as dosing durations increase has concluded that both chronic and acute DOX-induced cytotoxicity can be largely reduced with improved and targeted administration routes [21,38].…”
mentioning
confidence: 99%
“…In most cases, its treatment involves chemotherapy (1) . However, the drug toxicity and/or tumor cell resistance are obstacles to the choice of chemotherapy (2) . Scientific studies proved that combining chemotherapy with specific antioxidants, at defined dosages can improve drug efficacy and/or may reduce the severity of side effects (3,4) .…”
Section: Introductionmentioning
confidence: 99%